Orally administered intelligent self-ablating nanoparticles: a new approach to improve drug cellular uptake and intestinal absorption - Yanzi Liang; Ruihuan Ding; Huihui Wang; Lanze Liu; Jibiao He; Yuping Tao; Zhenyu Zhao; Jie Zhang; Aiping Wang; Kaoxiang Sun; Youxin Li; Yanan Shi (Taylor & Francis Group, 2022)
Oral drug delivery to treat diabetes is being increasingly researched. The mucus and the epithelial cell layers hinder drug delivery. We designed a self-ablating nanoparticle to achieve smart oral delivery to overcome the gastrointestinal barrier. We used the zwitterionic dilauroyl phosphatidylcholine, which exhibits a high affinity toward Oligopeptide transporter 1, to modify poly(lactic-co-glycolic acid) nanoparticles and load hemagglutinin-2 peptide to facilitate its escape from lysosomes. Nanoparticles exhibit a core-shell structure, the lipid layer is degraded by the lysosomes when the nanoparticles are captured by lysosomes, then the inner core of the nanoparticles gets exposed. The results revealed that the self-ablating nanoparticles exhibited higher encapsulation ability than the self-assembled nanoparticles (77% vs 64%) and with better stability. Quantitative cellular uptake, cellular uptake mechanisms, and trans-monolayer cellular were studied, and the results revealed that the cellular uptake achieved using the self-ablating nanoparticles was higher than self-assembling nanoparticles, and the number of uptake pathways via which the self-ablating nanoparticles functioned were higher than the self-assembling nanoparticles. Intestinal mucus permeation, in vivo intestinal circulation, was studied, and the results revealed that the small self-assembling nanoparticles exhibit a good extent of intestinal uptake in the presence of mucus. In vitro flip-flop, intestinal circulation revealed that the uptake of the self-ablating nanoparticles was 1.20 times higher than the self-assembled nanoparticles. Pharmacokinetic study and the pharmacodynamic study showed that the bioavailability and hypoglycemic effect of self-ablating nanoparticles were better than self-assembled nanoparticles.